High-Temperature Oxidation Of Titanium Aluminides - Amrin, Astuty (2005)

(untitled)
The high-temperature oxidation was performed on various compositions of Ti- Al based intermetallics, Ti-45Al, Ti-48Al and Ti-50Al(at%), and the ternary alloys, Ti-48Al-2Cr and Ti-48Al-4Cr (at%). The primary objectives of this research were to study the kinetics and mechanisms of the oxidation at temperatures of 700oC, 900oC and 1100oC. Oxidation experiments were conducted under isothermal conditions in flowing dry air and high-purity oxygen as well as thermal cyclic condition in flowing dry air. The scales formed during oxidation were generally complex and their morphologies and structures were influenced by the composition of the alloy and the exposure conditions and environment. Atomic Force Microscopy technique was employed to understand the surface topography of the thin oxide scales formed at the initial stage of oxidation. After isothermal exposure at 700oC in flowing dry air, all alloys exhibited protective oxidation, with larger weight gain observed for the ternary alloys, indicating that addition of chromium may have led to an increase in the oxidation rate. At 900oC, all alloys displayed paralinear behaviour with the ternary alloys exhibiting the fastest rate. Exposure at 1100oC resulted in the highest weight gain for binary alloys of Ti-45Al and Ti-48Al and the ternary alloys demonstrating parabolic oxidation, which indicates a protective behaviour. Crosssectional examination using energy dispersive x-ray spot and line-scan analysis of alloy Ti-50Al, Ti-48Al-2Cr and Ti-48Al-4Cr showed an Al-depletion region and a well-adhered oxide intact with the base alloy at the alloy-scale interface indicating outward diffusion of aluminium to form the Al2O3 scale. X-ray diffraction analysis revealed that the scales do not only consist of rutile-TiO2 and Î±-Al2O3 but also nitride compounds. Nano-indentation results showed that the oxide scales hardness were very much higher than the base-alloy by a factor of four. X-ray photoelectron spectroscopy analysis revealed that during transient stage of oxidation, the surface of the specimens was rich in Al2O3.